ANALISA POTENSI AKUIFER DI KECAMATAN RUMBAI PESISIR KOTA PEKANBARU DENGAN MENGGUNAKAN METODE GEOLISTRIK ATURAN SCHLUMBERGER - Miftakhudin Listianto; Riad Syech (Komunikasi Fisika Indonesia, 2020)
The analysis of aquifer potential has been done in the Rumbai Pesisir District of Pekanbaru City by using the Schlumberger configuration geoelectric method. Data was taken from four villages in Rumbai Pesisir Subdistrict, in Lembah Damai, Limbungan, Limbungan Baru and Meranti Pandak. The result obtained using progress software showed that each location has aquifer with different layer and thickness. The highest aquifer resistivity is located in Lembah Damai Village with a resistivity value of 549.50 Ωm in the third layer, while aquifer with the lowest resistivity value is located in Meranti Pandak Village with a resistivity value of 15.69 Ωm in the third layer. The highest thickness aquifer located in Meranti Pandak Village with a thickness of 48.47 m in the third layer, while the lowest thickness aquifer located in Limbungan Baru Village with a thickness of 11.51 m in the second layer. The Result from lithology of each path shows that flow pattern of water flowing from Lembah Damai Village to Limbungan Village, then Meranti Pandak Village and then Limbungan Baru Village. The results of the analysis of aquifers potential indicate that underground water reserves in the Rumbai Pesisir District of Pekanbaru City are 17.13 x 109 m³.